Analysis of 21st-century skills: Student collaboration through discovery learning in history subjects - Fauziyah, Fina; Amin, Saiful; Maulidiah, Linda (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
This research intends to describe the implementation of the discovery learning model and describe students' collaboration skills in history learning at MA Mambaul Ulum. The quantitative approach and descriptive approach were applied to this research. This research used a saturated sampling technique. A total of 28 students were used as samples in this study. Students' collaboration skills were obtained from observation sheets and supplemented with interview results. Data on students' collaboration skills were analyzed using descriptive statistical techniques. Based on the analysis results analysis results obtained from the observation sheet, it can be understood that the 28 students are 18 trained and high level, while the rest are in the category of medium and basic level. All indicators of collaboration skills have a high except the time management indicator, which is a very high category. This research concludes that the discovery learning model can hone students' collaboration skills.